INTEGRAL ASSESSMENT OF POPULATION HEALTH IN THE REGIONS OF THE KYRGYZ REPUBLIC: MEDICAL AND DEMOGRAPHIC ASPECT (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
To assess the level of health of the population in the regions of the Kyrgyz Republic,a system of private medical and demographic indicators was proposed and an integral indicator ofhealth was calculated. The calculation results showed that during 2005-2018 among the leaders«with a high level of health» were Batken, Osh and Talas regions. Jalal-Abad region in 2005 wasin the group of regions «with a high level of health», by 2018 it switched to an «average level ofhealth», while Osh city - on the contrary, «from an average level of health» to a «high level of health».The outsiders «with a low level of health» were Issyk-Kul, Naryn, Chui regions and Bishkek city.
Keywords: medico-demographic aspect, integral indicator of health.